Diagnostic Value of the lncRNA NEAT1 in Peripheral Blood Mononuclear Cells of Patients with Sepsis - Huang, Shuying; Qian, Kejian; Zhu, Yuanfang; Huang, Zikun; Luo, Qing; Qing, Cheng (Disease Markers, 2017)
Background. This study aims to evaluate the diagnostic value of nuclear-enriched abundant transcript 1 (NEAT1) expression in peripheral blood mononuclear cells (PBMCs) for the early diagnosis of sepsis. Methods. A total of 59 patients with sepsis, 52 noninfectious SIRS patients, and 56 healthy controls were recruited fort this study. The levels of NEAT1 expression in PBMCs were measured using quantitative real-time polymerase chain reaction (qRT-PCR). Results. Compared with healthy controls, NEAT1 expression of PBMCs in sepsis and SIRS groups were significantly increased (3.76 ± 0.71- and 1.64 ± 0.43-fold, resp.) (P<0.01), but NEAT1 levels are significantly lower in the SIRS group than in the sepsis group, and there was no statistical significant relevance between survivors and nonsurvivors in patients with sepsis. NEAT1 with an area under the curve (AUC) of 0.851 (95% CI: 0.812–0.935) indicated sensitivity (67.85%) and specificity (87.27%) for the diagnosis for sepsis, the positive predictive value (PPV) was 83.3%, and the negative predictive value (NPV) was 71.6%. The AUC for NEAT1 in the diagnosis of SIRS versus healthy controls was 0.755 (95% CI: 0.664–0.847), with 69.23% sensitivity and 70.91% specificity, the PPV was 72.3%, and the NPV was 72.49%. Conclusion. Measurement of NEAT1 expression in PBMCs could be considered as a good additive marker for the diagnosis of sepsis.